Examining the increased prevalence of food hypersensitivities - Brainerd, Amanda (Kansas State University, 2022)
The prevalence of reported food hypersensitivities has been increasing among both adults and children in the United States. Data that accurately reflect the prevalence of food hypersensitivities are limited due to diagnostic challenges, potentially leading to increased use of non-validated testing procedures. The current review examines food hypersensitivities, focusing on the validity of diagnostic methods, the effects of food processing on allergenicity, and the impact of health literacy in reporting food hypersensitivities. We further consider how increases in food hypersensitivities influence federal and educational institutional policies, industry practices, and affected individuals as well as those around them. Advancements in food processing techniques have influenced the allergenicity of proteins within common allergenic foods. In addition, health literacy may be a barrier to public understanding of health information, including information related to food hypersensitivities. The increase in the prevalence of food hypersensitivities impacts nationwide policies and practices through new federal regulations such as the FASTER Act, impacting accommodations in educational facilities, increasing the market for allergen-free products, and expanding manufacturer labeling. Ultimately, these changes may affect individuals with food hypersensitivities including increased food avoidance and economic burdens. Future studies are necessary to determine whether alternative food hypersensitivity testing can be utilized to positively identify food hypersensitivities and what effect processing has on the allergenicity of certain foods. Similarly, future research is required to assess the impact of the increased prevalence of food hypersensitivities on federal and educational institutional policies, industry practices, and individuals diagnosed with food hypersensitivities as well as those around them.
Keywords: Food hypersensitivities; Food allergy; Food intolerance